Liquid crystal compound and preparation method and application thereof
By preparing liquid crystal compounds with specific structures and applying them in liquid crystal compositions, the shortcomings of existing liquid crystal materials in rapid response and low driving voltage are solved, and the liquid crystal display effect with high dielectric anisotropy and fast response are achieved. In a variety of LCD displays.
Patent Information
- Application Number
- CN202411172611.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-17
AI Technical Summary
Existing liquid crystal materials have shortcomings in fast response and low driving voltage, which is difficult to meet the increasing demand for display technology, especially in TFT-LCD products, which require higher dielectric anisotropy, liquid crystal mutual solubility and refractive index. Anisotropy.
Provided is a liquid crystal compound with a specific structure, which is prepared by four synthesis reaction steps, including reaction of an organolithium reagent with a methyl reagent, a borate ester and an oxidizing agent, combined with a dehydrating agent, to prepare a high dielectric anisotropy and Liquid crystal compounds with good liquid crystal mutual solubleness and are used in liquid crystal compositions to improve dielectric anisotropy and response speed.
It significantly improves the dielectric anisotropy and response speed of the liquid crystal composition, while reducing the driving voltage. It is suitable for various liquid crystal displays, including TN, ADS, VA, PSVA, FFS or IPS liquid crystal displays, and has broad application prospects.
Smart Images

Figure CN119144345A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid crystal display materials, and in particular to a liquid crystal compound and a preparation method and application thereof. Background Art
[0002] Liquid crystal materials, as environmental materials, have great research value and bright application prospects in the fields of information display materials, organic optoelectronic materials, etc. As new display materials, liquid crystal materials have many advantages, such as extremely low power consumption and low driving voltage. At the same time, compared with other materials, they also have the advantages of small size, light weight, long life, large display information volume, and no electromagnetic radiation. They can almost meet the requirements of various information displays, especially in TFT-LCD (thin film transistor technology) products.
[0003] Liquid crystal materials are required to have good chemical and thermal stability, good stability to electric fields and electromagnetic radiation, a wide nematic phase temperature range, appropriate refractive index and dielectric anisotropy, a fast response speed and a high voltage holding rate.
[0004] At present, TFT-LCD product technology has matured and successfully solved technical problems such as viewing angle, resolution, color saturation and brightness. Large-size and small- and medium-size TFT-LCD displays have gradually occupied the mainstream position of flat panel displays in their respective fields. However, the requirements for display technology have been constantly increasing, requiring liquid crystal displays to achieve faster response, reduce driving voltage to reduce power consumption, etc. With the development of display technology, higher requirements have been put forward for liquid crystal materials, especially in terms of fast response, lower driving voltage, and lower power consumption.
[0005] In order to improve the performance of materials to adapt them to new requirements, the synthesis of new structural liquid crystal compounds and the study of structure-property relationships have become an important task in the liquid crystal field. Summary of the invention
[0006] The present invention provides a liquid crystal compound and a preparation method and application thereof. The liquid crystal compound has the advantages of higher dielectric anisotropy, good liquid crystal mutual solubility and the like, and has important application value.
[0007] According to a first aspect of the present invention, the present invention provides a liquid crystal compound having a structure shown in the following general formula I: (I)
[0008] wherein R1 represents H, an alkyl group of 1 to 12 carbon atoms, or an alkoxy group of 1 to 12 carbon atoms, one or more hydrogen atoms in the alkyl group of 1 to 12 carbon atoms or the alkoxy group of 1 to 12 carbon atoms may be optionally substituted by halogen, and one or more -CH2- may each independently be replaced by -C≡C-, -CH=CH-, -CF=CF-, -CF=CH-, -COO-, -OCO- or -O- in a manner that the O atoms are not directly connected to each other; Ring A and Ring B each independently represent 1,4-phenylene, 1,4-cyclohexylene, 1,4-cyclohexenylene, 1,4-phenylene in which 1 to 4 hydrogen atoms are substituted by fluorine atoms, cycloalkyl of 3 to 6 carbon atoms, or cycloalkanediyl of 3 to 6 carbon atoms; wherein one or more hydrogen atoms in the cycloalkyl of 3 to 6 carbon atoms or cycloalkanediyl of 3 to 6 carbon atoms may be optionally substituted by fluorine atoms; m is 0, 1 or 2, n is 0 or 1, and m and n are not 0 at the same time.
[0009] The liquid crystal compound of the specific structure of the present invention has the advantages of higher dielectric anisotropy, good liquid crystal mutual solubility, etc. The liquid crystal compound of the present invention is specifically applied to the liquid crystal composition of the conventional system, which can significantly improve the dielectric anisotropy △ε of the liquid crystal composition while maintaining an appropriate refractive index anisotropy △n. The obtained liquid crystal composition has significant fast response characteristics and low voltage driving characteristics.
[0010] In order to further improve the performance of the liquid crystal compound, further, the R1 represents H or an alkyl group having 1-5 carbon atoms or an alkoxy group having 1-5 carbon atoms; the ring A and the ring B each independently represent 1,4-phenylene, 1,4-cyclohexylene or 1,4-phenylene in which 1-4 hydrogen atoms are substituted by fluorine atoms.
[0011] In order to further improve the performance of the liquid crystal compound, further, the liquid crystal compound is selected from one of the following compounds:
[0012] According to the second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned liquid crystal compound, and the synthesis route is as follows: ; The specific steps include: Step (1): By reacting the first organic lithium reagent with the methyl reagent, ; Step (2): Reaction with a second organolithium reagent, and then with a boric ester, to obtain ; Step (3): Through oxidation reaction with oxidant, ; Step (4): And the result obtained in step (3) As the raw material reaction, we get ; Among them, R1, m, n, ring A, and ring B in the compounds involved in each step correspond to the groups represented by R1, m, n, ring A, and ring B in the liquid crystal compound.
[0013] In the above scheme, the raw materials for preparing the liquid crystal compound of the present invention are easily available, and the method includes four synthesis reaction steps. Each synthesis reaction is easy to control. The whole preparation method is simple and applicable to wide promotion.
[0014] Furthermore, in the step (1), , the molar ratio of the first organic lithium reagent to the methyl reagent is 1: (1.0-1.8): (1.0-2.0), and the reaction temperature is -50--100°C; The first organic lithium reagent is selected from one or more of n-butyl lithium, sec-butyl lithium, tert-butyl lithium or n-butyl lithium and potassium tert-butoxide; the methyl reagent is selected from one or more of methyl iodide, methyl bromide, dimethyl carbonate or dimethyl sulfate.
[0015] In the above scheme, the reaction efficiency can be improved by reasonably controlling the type and dosage ratio of each raw material and the reaction in step (1).
[0016] Furthermore, in step (2), , the molar ratio of the second organic lithium reagent to the borate ester is 1: (1.0-1.8): (1.0-2.0), and the reaction temperature is -50--100°C; Wherein, the second organic lithium reagent is selected from one or more of n-butyl lithium, sec-butyl lithium, tert-butyl lithium or n-butyl lithium and potassium tert-butoxide; the borate ester is selected from one or more of trimethyl borate, triisopropyl borate, tributyl borate or triisobutyl borate.
[0017] In the above scheme, the reaction efficiency can be improved by reasonably controlling the type and dosage ratio of each raw material and the reaction in step (2).
[0018] Furthermore, in step (3), The molar ratio of the oxidant to the oxidant is 1: (1.0-4.0), and the reaction temperature is 40-80° C.; the oxidant is selected from hydrogen peroxide or meta-chloroperbenzoic acid, preferably hydrogen peroxide.
[0019] In the above scheme, the reaction efficiency can be improved by reasonably controlling the type and dosage ratio of each raw material and the reaction in step (3).
[0020] Furthermore, in step (4), and Under the action of a dehydrating agent, the reaction is obtained ; in, , The molar ratio of the dehydrating agent to the dehydrating agent is 1: (1.0-2.0): (1.0-3.0), and the reaction temperature is -10-50° C.; preferably, the dehydrating agent is N,N'-diisopropylcarbodiimide.
[0021] In the above scheme, the reaction efficiency can be improved by reasonably controlling the type and dosage ratio of each raw material and the reaction in step (4).
[0022] The preparation method of the present invention may involve conventional post-treatment when necessary, and the conventional post-treatment may specifically include: extraction with dichloromethane, ethyl acetate or toluene, separation, washing with water, drying, evaporation with a vacuum rotary evaporator, and purification of the obtained product by reduced pressure distillation or recrystallization and / or chromatographic separation.
[0023] The above preparation method can stably and efficiently obtain the liquid crystal compound of the present invention.
[0024] According to the third aspect of the present invention, the present invention further provides a liquid crystal composition, comprising the above-mentioned liquid crystal compound; the mass percentage of the liquid crystal compound in the liquid crystal composition is 1~60%, preferably 3~50%, and more preferably 5~25%.
[0025] According to a fourth aspect of the present invention, the present invention also provides the use of the above-mentioned liquid crystal compound in a liquid crystal display device. Optionally, the liquid crystal display device includes but is not limited to TN, ADS, VA, PSVA, FFS or IPS liquid crystal displays.
[0026] The present invention provides a liquid crystal compound, which has extremely high negative dielectric anisotropy and low rotational viscosity by using the liquid crystal compound or a composition containing the liquid crystal compound, thereby effectively reducing the driving voltage and improving the response speed of the liquid crystal display device. At the same time, it has the characteristics of moderate optical anisotropy value, high charge retention rate, etc. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.
[0029] Unless otherwise specified, the raw materials can be obtained from public commercial channels.
[0030] According to conventional detection methods in the art, various performance parameters of the liquid crystal compound are obtained by linear fitting, wherein the specific meanings of the various performance parameters are as follows: △n represents optical anisotropy (25℃); △ε represents dielectric anisotropy (25℃, 1000Hz); γ1 represents rotational viscosity (mPa.s, 25℃); CP represents clearing point (℃).
[0031] Example 1
[0032] This embodiment provides a liquid crystal composition, the structural formula of which is: BYLC-01.
[0033] The synthetic route for preparing compound BYLC-01 is as follows: .
[0034] The specific steps are as follows: (1) Synthesis of compound BYLC-01-1: Under nitrogen protection, 40.0 g of 2-fluoro-4-bromobenzonitrile and 280 ml of tetrahydrofuran were added to the reaction bottle, and 0.24 mol of n-butyl lithium in n-hexane solution was added dropwise at -70 to -80 °C. After the addition, the reaction was kept warm for 1 hour, and 38.3 g of iodomethane was added dropwise at -70 to -80 °C, and then the temperature was naturally returned to -30 °C. 300 ml of saturated sodium bisulfite aqueous solution was added for hydrolysis, and conventional post-treatment was performed. 38.5 g of light yellow liquid (compound BYLC-01-1) was purified by column chromatography, GC: 98.5%, and the yield was 90%.
[0035] (2) Synthesis of compound BYLC-01-2: Under nitrogen protection, 32.0g BYLC-01-1 and 150ml tetrahydrofuran were added to the reaction bottle, and 0.18mol n-butyl lithium in n-hexane solution was added dropwise at -70~-80℃. After the addition, the mixture was kept warm for 1 hour, and 23.4g trimethyl borate was added dropwise at -70~-80℃, and then the temperature was naturally returned to -30℃. 300ml of 2M hydrochloric acid aqueous solution was added for acidification, and conventional post-treatment was performed. Recrystallization from petroleum ether gave 23.6g of a light yellow solid (compound BYLC-01-2), HPLC: 98.5%, yield 88%.
[0036] (3) Synthesis of compound BYLC-01-3: Add 23.2g of compound BYLC-01-2 and 100ml of tetrahydrofuran to the reaction flask, add 0.26mol of hydrogen peroxide dropwise under reflux, and reflux for 1 hour. Perform conventional post-treatment to obtain 18.6g of light pink solid (compound BYLC-01-3), GC: 99.2%, yield 95%.
[0037] (4) Synthesis of compound BYLC-01: Under nitrogen protection, 18.1 g of compound BYLC-01-3, 18.7 g of ethylcyclohexylcarboxylic acid, 3 g of 4-dimethylaminopyridine, and 100 ml of dichloromethane were added to the reaction bottle, and 17.7 g of DIC was added dropwise at a temperature of -5~5°C. After the addition, the reaction was kept warm for 0.5 hour, and the temperature was naturally raised. The reaction was allowed to react at room temperature for 3 hours. 100 ml of water was added to quench the reaction, and conventional post-treatment was performed to obtain 29.6 g of a white solid (compound BYLC-01), GC: 99.6%, and a yield of 85.4%.
[0038] The obtained white solid BYLC-01 was analyzed by GC-MS, and the m / z of the product was 289.1 (M+).
[0039] 1 H-NMR (300MHz, CDCl3): 0.85-1.90(m,14H), 2.15-2.94(m,4H), 7.10-7.85(m,2H).
[0040] Example 2
[0041] This embodiment provides a liquid crystal composition, the structural formula of which is: BYLC-02.
[0042] The synthetic route for preparing compound BYLC-02 is as follows: .
[0043] The specific steps are as follows: Synthesis of compound BYLC-02: Under nitrogen protection, 30.2 g of compound BYLC-01-3, 47.6 g of ethylbiscyclohexylcarboxylic acid, 3.6 g of 4-dimethylaminopyridine, and 150 ml of dichloromethane were added to the reaction bottle, and 28.5 g of DIC was added dropwise at a temperature of -5~5°C. After the addition, the reaction was kept warm for 0.5 hour, and the temperature was naturally raised. The reaction was allowed to react at room temperature for 3 hours. 200 ml of water was added to quench the reaction, and conventional post-treatment was performed to obtain 63.9 g of a white solid (compound BYLC-02), GC: 99.7%, and a yield of 86.2%.
[0044] The obtained white solid BYLC-02 was analyzed by GC-MS, and the m / z of the product was 371.1 (M+).
[0045] 1H-NMR (300MHz, CDCl3): 0.85-1.90(m,24H), 2.15-2.94(m,4H), 7.10-7.85(m,2H).
[0046] Example 3
[0047] This embodiment provides a liquid crystal composition, the structural formula of which is: BYLC-03.
[0048] The synthetic route for preparing compound BYLC-03 is as follows: .
[0049] The specific steps are as follows: Synthesis of compound BYLC-03: Under nitrogen protection, 22.6 g of compound BYLC-01-3, 36.9 g of propylcyclohexylbenzoic acid, 2.7 g of 4-dimethylaminopyridine, and 150 ml of dichloromethane were added to the reaction bottle, and 26.0 g of DIC was added dropwise at a temperature of -5~5°C. After the addition, the mixture was kept warm for 0.5 hours, and the temperature was naturally raised. The mixture was reacted at room temperature for 3 hours. 200 ml of water was added to quench the reaction, and conventional post-treatment was performed to obtain 50.3 g of a white solid (compound BYLC-03), GC: 99.5%, and the yield was 88.5%; The obtained white solid BYLC-03 was analyzed by GC-MS, and the m / z of the product was 379.1 (M+).
[0050] 1 H-NMR (300MHz, CDCl3): 0.85-1.90(m,16H), 2.15-2.94(m,4H), 7.10-7.85(m,4H), 7.95-8.95(m,2H).
[0051] According to the technical solutions of Example 1 and Example 2, the following liquid crystal compounds can be synthesized by simply replacing the corresponding raw materials without changing any substantial operations.
[0052] Example 4
[0053] This embodiment provides a liquid crystal composition, the structural formula of which is: BYLC-04.
[0054] The obtained white solid BYLC-04 was analyzed by GC-MS, and the m / z of the product was 293.1 (M+).
[0055] 1 H-NMR (300MHz, CDCl3): 0.85-1.90(m,12H), 2.15-2.94(m,4H), 7.10-7.85(m,1H).
[0056] Example 5
[0057] This embodiment provides a liquid crystal composition, the structural formula of which is: BYLC-05.
[0058] The obtained white solid BYLC-05 was analyzed by GC-MS, and the m / z of the product was 297.1 (M+).
[0059] 1 H-NMR (300MHz, CDCl3): 0.85-1.90(m,5H), 2.15-2.94(m,5H), 6.75-7.75(m,4H), 7.95-8.75(m,2H).
[0060] Example 6
[0061] This embodiment provides a liquid crystal composition, the structural formula of which is: BYLC-06.
[0062] The obtained white solid BYLC-06 was analyzed by GC-MS, and the m / z of the product was 385.1 (M+).
[0063] 1 H-NMR (300MHz, CDCl3): 0.85-1.90(m,26H), 2.15-2.94(m,4H), 7.10-7.85(m,2H).
[0064] Comparative Example 1
[0065] This comparative example provides a liquid crystal composition, the structural formula of which is: .
[0066] Comparative Example 2
[0067] This comparative example provides a liquid crystal composition, the structural formula of which is: .
[0068] Experimental Example 1
[0069] The performance parameter data of the liquid crystal compounds of Examples 1-6, Comparative Example 1 and Comparative Example 2 were compared and sorted, and the test results are shown in Table 1: Table 1: Performance test results of liquid crystal compounds
[0070] It can be clearly seen from the test results in Table 1 that the liquid crystal compound provided by the present invention has the advantage of large dielectric anisotropy.
[0071] Experimental Example 2
[0072] The liquid crystal compounds of Example 2 and Comparative Example 2 were added to the liquid crystal composition BYHJ-1 at a ratio of 8% by weight, respectively. The composition of the liquid crystal composition BYHJ-1 is shown in Table 2 below, and liquid crystal compositions BYHJ-11 and BYHJ-22 were obtained, respectively.
[0073] Table 2 Weight percentage of each component of BYHJ-1 liquid crystal composition
[0074] The solubility of the above liquid crystal compositions BYHJ-11 and BYHJ-22 was tested respectively, and the test results are shown in Table 3: Table 3: Solubility test results of liquid crystal compositions
[0075] It can be clearly seen from the test results in Table 3 that the liquid crystal compound provided by the present invention has better solubility in the liquid crystal composition than the traditional compound with similar chemical structure.
[0076] It can be clearly seen from the test results in Tables 1 and 3 that the liquid crystal compound provided by the present invention has the characteristics of large dielectric anisotropy, good mutual solubility and stable performance compared with traditional compounds with similar chemical structures. After being applied to liquid crystal compositions, the driving voltage of the device can be reduced, and it has broad application prospects.
[0077] In addition, after the liquid crystal compound provided by the present invention is specifically applied to a liquid crystal composition of a conventional system, it is found that it can significantly improve the dielectric anisotropy Δε of the liquid crystal composition while maintaining an appropriate refractive index anisotropy Δn. The resulting liquid crystal composition has significant fast response characteristics and low voltage driving characteristics.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A liquid crystal compound, characterized in that: It has the structure shown in the following general formula I: (I) wherein R1 represents H, an alkyl group of 1 to 12 carbon atoms, or an alkoxy group of 1 to 12 carbon atoms, one or more hydrogen atoms in the alkyl group of 1 to 12 carbon atoms or the alkoxy group of 1 to 12 carbon atoms may be optionally substituted by halogen, and one or more -CH2- may each independently be replaced by -C≡C-, -CH=CH-, -CF=CF-, -CF=CH-, -COO-, -OCO- or -O- in a manner that the O atoms are not directly connected to each other; Ring A and Ring B each independently represent 1,4-phenylene, 1,4-cyclohexylene, 1,4-cyclohexenylene, 1,4-phenylene in which 1 to 4 hydrogen atoms are substituted by fluorine atoms, cycloalkyl of 3 to 6 carbon atoms, or cycloalkanediyl of 3 to 6 carbon atoms; wherein one or more hydrogen atoms in the cycloalkyl of 3 to 6 carbon atoms or cycloalkanediyl of 3 to 6 carbon atoms may be optionally substituted by fluorine atoms; m is 0, 1 or 2, n is 0 or 1, and m and n are not 0 at the same time.
2. The liquid crystal compound according to claim 1, characterized in that The R1 represents H or an alkyl group having 1 to 5 carbon atoms or an alkoxy group having 1 to 5 carbon atoms; the ring A and the ring B each independently represent a 1,4-phenylene group, a 1,4-cyclohexylene group or a 1,4-phenylene group in which 1 to 4 hydrogen atoms are substituted by fluorine atoms.
3. The liquid crystal compound according to claim 1, characterized in that The liquid crystal compound is selected from one of the following compounds: 。 4. The method for preparing a liquid crystal compound according to any one of claims 1 to 3, characterized in that: The synthetic route is as follows: ; The specific steps include: Step (1): By reacting the first organic lithium reagent with the methyl reagent, ; Step (2): Reaction with a second organolithium reagent, and then with a boric ester, to obtain ; Step (3): Through oxidation reaction with oxidant, ; Step (4): And the result obtained in step (3) As the raw material reaction, we get ; Wherein, R1, m, n, ring A and ring B in the compounds involved in each step correspond to the groups represented by R1, m, n, ring A and ring B in the liquid crystal compound.
5. The preparation method according to claim 4, characterized in that: In the step (1), , the molar ratio of the first organic lithium reagent to the methyl reagent is 1: (1.0-1.8): (1.0-2.0), and the reaction temperature is -50--100°C; The first organic lithium reagent is selected from one or more of n-butyl lithium, sec-butyl lithium, tert-butyl lithium or n-butyl lithium and potassium tert-butoxide; the methyl reagent is selected from one or more of methyl iodide, methyl bromide, dimethyl carbonate or dimethyl sulfate.
6. The preparation method according to claim 4, characterized in that: In the step (2), , the molar ratio of the second organic lithium reagent to the borate ester is 1: (1.0-1.8): (1.0-2.0), and the reaction temperature is -50--100°C; Wherein, the second organic lithium reagent is selected from one or more of n-butyl lithium, sec-butyl lithium, tert-butyl lithium or n-butyl lithium and potassium tert-butoxide; the borate ester is selected from one or more of trimethyl borate, triisopropyl borate, tributyl borate or triisobutyl borate.
7. The preparation method according to claim 4, characterized in that: In the step (3), The molar ratio of the oxidant to the oxidant is 1: (1.0-4.0), and the reaction temperature is 40-80° C.; the oxidant is selected from hydrogen peroxide or meta-chloroperbenzoic acid, preferably hydrogen peroxide.
8. The preparation method according to claim 4, characterized in that: In the step (4), and Under the action of a dehydrating agent, the reaction is obtained ; in, , The molar ratio of the dehydrating agent to the dehydrating agent is 1: (1.0-2.0): (1.0-3.0), and the reaction temperature is -10-50° C.; preferably, the dehydrating agent is N,N'-diisopropylcarbodiimide.
9. A liquid crystal composition, characterized in that: The composition comprises the liquid crystal compound according to any one of claims 1 to 3; the mass percentage of the liquid crystal compound in the liquid crystal composition is 1 to 60%, preferably 3 to 50%, and more preferably 5 to 25%.
10. Use of the liquid crystal compound according to any one of claims 1 to 3 in a liquid crystal display device.
Citation Information
Cited By
Liquid crystal compound, preparation method therefor, and use thereof
WO2026045894A1
